Concurrent Access Algorithms for Different Data Structures: A Research Review - Parminder Kaur (JURNAL MAHAJANA INFORMASI, 2017)
Algorithms refers to a finite set of steps, which when followed solves a number of problems and algorithams for concurrent data structure have gained attention in recent years as multi-core processors have become ubiquitous. Several features of shared-memory multiprocessors make concurrent data structures significantly more difficult to design and to verify as correct than their sequential counterparts. The primary source of this additional difficulty is concurrency. This paper provides an overview of the some concurrent access algorithms for different data structures. Keywords: concurrency, lock-free, non-blocking, mem-ory management, compares and swap, elimination